16-Channel Integrated Potentiostat for Distributed Neurochemical Sensing - Genov, R.; Stanacevic, M.; Naware, M.; Cauwenberghs, G.; Thakor, N.V. (IEEE transactions on circuits and systems. I, Regular papers, 2006)
We present the architecture and VLSI circuit implementation of a BiCMOS potentiostat bank for monitoring neurotransmitter concentration on a screen-printed carbon electrode array. The potentiostat performs simultaneous acquisition of bidirectional reduction-oxidation currents proportional to neurotransmitter concentration on 16 independent channels at controlled redox potentials. Programmable current gain control yields over 100-dB cross-scale dynamic range with 46-pA input-referred rms noise over 12-kHz bandwidth. The cutoff frequency of a second-order log-domain anti-aliasing filter ranges from 50 Hz to 400 kHz. Track-and-hold current integration is triggered at the sampling rate between dc and 200 kHz. A 2.25-mmtimes2.25-mm prototype was fabricated in a 1.2-mum VLSI technology and dissipates 12.5 mW. Chronoamperometry dopamine concentration measurements results are given. Other types of neurotransmitters can be selected by adjusting the redox potential on the electrodes and the surface properties of the sensor coating